Determination of Ivermectin in Medicated Feeds by Liquid Chromatography with Fluorescence Detection - Konrad Pietruk; Piotr Jedziniak (The Scientific World Journal)
A labour- and time-effective analytical procedure for determination of ivermectin in medicated feed at recommended level of 2.0 mg kg−1 has been developed and validated. The analyte was extracted from grinded feed samples with acetonitrile and derivatisated with N-methylimidazole and trifluoracetic anhydride. The fluorescent derivatives were analysed by liquid chromatography method using C8 column. The isocratic conditions using acetonitrile, methanol, water, and tetrahydrofuran were applied. Fluorescence detection was performed at 365 nm (excitation) and 475 nm (emission) wavelengths. The total analysis time was 10 min. The validation results of the method (within-laboratory reproducibility 4.0% CV, mean recovery 100.1%) confirm the appropriate precision and accuracy of the developed method.